Modelling of phenolic resin polymerisation - Riccardi, Carmen Cristina (2002)
The kinetics of the polymerisation of resol-type phenolic resins has been modelled taking into account the phenol and formaldehyde equilibria. The kinetic parameters were obtained by adjusting the experimental evolution of phenol, formaldehyde and initial addition products during synthesis. The influence of the type and amount of catalyst, the initial pH, the initial formaldehyde-to-phenol molar ratio and the condensation temperature, on the kinetics rate constants was quantified.